Formulation And Antioxidant Property Of Bitter Melon Seeds Oil Loaded Into SNEDDS Systems As A Nutraceutical - Lina Winarti; Lusia Oktora Ruma Kumala Sari; Evi Umayah Ulfa; Dwi Ayu Samsuri (Universitas Gadjah Mada, 2021)
Bitter melon seeds oil is less soluble in the gastrointestinal tract and has low absorption. Therefore, a self-nanoemulsion dosage form needed to support its absorption and increase its stability. This study aimed to formulate bitter melon seeds oil into a self-nano emulsifying drug delivery system (SNEDDS) and evaluate its antioxidant activity using the Ferric Reducing Antioxidant Power (FRAP) method. The SNEDDS formulation uses bitter melon seed oil as the active ingredient and the oil phase, cremophor RH 40 as a surfactant, and glycerin as a co-surfactant. The results showed that the best SNEDDS formula obtains a ratio of oil: Smix (surfactant mixture) of 1:4. The best formula transmittance was 97.35 ± 0.04% with an emulsification time of 15.69 ± 0.06 seconds, a pH value of 6.87 ± 0.08, and a particle size of 31.8 ± 16.3 nm. Thermodynamic stability and robustness to dilution tests show the preparation is stable and resistant to various dilutions and pH. The antioxidant activity of bitter melon seed oil before and after being formulated into SNEDDS resulted in 62.73% and 50.31% reducing power. This result is not differences significantly. This study concluded that bitter melon seeds oil SNEDDS has good physical characteristics, stability, and no antioxidant activity changes.